Pemanfaatan Teknik Informatika dan Komunikasi pada Peserta Didik Kelas VI Madrasah Ibtida’iyyah Al-Huda Sidoarjo - Awaludin Jamil; Ana Safitri; Kuunu Ghurron Muhajjalina; Nanang Zamroji (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This qualitative case study research examines the utilization of Information and Communication Technology (ICT) by grade VI students of MI Al-Huda Sidoarjo based on constructivism theory. Data from observations, interviews, and documentation show ICT as a cognitive partner that facilitates independent exploration and construction of knowledge. Teachers act as facilitators, increasing engagement, independence, and understanding of Islamic values. The utilization of ICT has a positive impact on students’ learning motivation and development of 21st century skills holistically.